KAJIAN DAMPAK LINGKUNGAN PADA PEMBANGUNAN INFRASTRUKTUR BLOK OFFICE KABUPATEN MALANG - G D. Pandulu; Suhudi Suhudi (BUANA SAINS, 2012)
By the decision that Kepanjen District becomes the capital of Malang Regency, there will be displacement of governmental infrastructure, from Malang City to Kepajen District, Malang Regency. One of infrastructures that will be built there is the Office Block in Penarukan Village and Panggungrejo Village. In the utilization of natural resources, the Government of Malang Regency takes wisdom of environmentally sustainable development. The purpose of this study is to identify effect at were actifity to environmental component, predict the impacts on the environment component, and compose prevention, mitigation, and control the negative impacts. This study is used descriptive qualitative and quantitative analysis. Based on the analysis of chemical components of geophysics, slope of 0-2%, alluvial soil, ambient air quality, and noise remained below standard of ambient air quality specified under the Rule of Governor of East Java No. 10/2009, clean water quality of inhabitant and clean water quality of river are still below standard of traffic analysis on Panji Streat is at the service level C. The environmental management direction at the pre construction stage are by using social approach and inviting a survey expert and measurement equipments which have been certified, construction stage, and post construction by social and technological approach by implementing Standard Operation Procedures